1990
DOI: 10.1007/bf00300780
|View full text |Cite
|
Sign up to set email alerts
|

Rat urinary bladder carcinomas induced by N-butyl-N-(4-hydroxybutyl)-nitrosamine and N-methyl-N-nitrosourea

Abstract: The present investigation was conducted to examine the combination effect of N-butyl-N-(4-hydroxy-butyl)nitrosamine(BBN) and N-methyl-N-nitrosourea(MNU) in rat urinary bladder carcinogenesis. Experiment 1 was performed in the groups treated by oral BBN administration in combination with MNU intravesical instillation and their control groups. In the groups given both BBN and MNU, the ratio of rats with the nonpapillary type to carcinoma-bearing rats was significantly higher than in the controls. Since most of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Previous studies indicate that low doses of BBN induce tumors in the urothelium of rats and mice [Cohen 1998[Cohen , 2002, while MNU induces bladder cancer rapidly only after repeated instillation directly into the bladder [Hicks, 1980]. Some studies have been undertaken to evaluate the association between an additional treatment with MNU on the extent of invasion and H-ras and p53 mutations in TCC from rats bearing BBN-induced bladder neoplasias [Ozono et al, 1990;Shibata et al, 1994;Ozaki et al, 1997]. Although there were relatively few animals in the BBN-only group, our findings suggest that the MNU treatments promoted mouse bladder carcinogenesis since there was an increased frequency of invasive TCC in BBN/MNU-treated groups when compared with BBNonly.…”
mentioning
confidence: 99%
“…Previous studies indicate that low doses of BBN induce tumors in the urothelium of rats and mice [Cohen 1998[Cohen , 2002, while MNU induces bladder cancer rapidly only after repeated instillation directly into the bladder [Hicks, 1980]. Some studies have been undertaken to evaluate the association between an additional treatment with MNU on the extent of invasion and H-ras and p53 mutations in TCC from rats bearing BBN-induced bladder neoplasias [Ozono et al, 1990;Shibata et al, 1994;Ozaki et al, 1997]. Although there were relatively few animals in the BBN-only group, our findings suggest that the MNU treatments promoted mouse bladder carcinogenesis since there was an increased frequency of invasive TCC in BBN/MNU-treated groups when compared with BBNonly.…”
mentioning
confidence: 99%
“…However, significant tumor suppression was detected only in the BC31 xenograft model. In the BBN‐induced rat bladder cancer model, the incidence and size of tumors have been reported to be in accordance with concentration, duration and post–duration of BBN intake . The present study set a BBN intake for 10 weeks followed by 20 weeks of luteolin administration.…”
Section: Discussionmentioning
confidence: 99%
“…Druckrey et al [9] first described the carcinogenic effect of N‐butyl‐N‐(4‐hydroxybutyl) nitrosamine (BBN) on the rat urinary bladder. Since then, this model system has been used by many investigators to study the histogenesis and the effects of various agents on the tumorigenesis and growth of bladder tumours [10–12]. In a preliminary experiment, we found that when 0.05% BBN was administered to rats daily for 8 weeks, bladder tumours developed in all rats and by the 20th week, 70–80% of these tumours were carcinomas.…”
Section: Introductionmentioning
confidence: 94%